The origins of Midrash: from teaching to text - Mandel, Paul D. (Supplements to the Journal for the Study of Judaism Ser, 2017)
Contents -- Acknowledgments -- Abbreviations -- Introduction -- 1 Introducing the Book -- 2 Methodological Considerations -- 3 The Plan of the Book -- Part 1 Darash and the Jewish Leaders of the Second Temple Period -- Chapter 2 The Scribe (sofer) in the Second Temple Period -- 1 The Scribe as Writing Professional -- 2 The Early Mesopotamian Scribe or ṭupšarru: Accountant and Tallyman -- 3 The West-Semitic Scribe or spr: Recorder -- 4 The Post-Exilic sofer: Ezra as safar dataʾ or Law Interpreter, Instructor and Advisor -- 5 safar and sofer in Other Texts of the Second Temple Period: Corroborative Evidence -- 6 The sofer in Sirach and Other Hebrew Passages of the Second Temple Period -- 7 The sofer in a Leadership Role in Jewish Society of the Late Second Temple Period -- 8 The Meaning of darash in Late Biblical Hebrew -- 9 Conclusions -- Excursus: The Figure of sofer in the Jewish Apocalyptic Tradition of the Second Temple Period -- Chapter 3 Doresh ha-torah and midrash torah: Teaching and Interpretation in the Dead Sea Scrolls -- 1 Introduction -- 2 midrash ha-torah and doresh ha-torah in the Dead Sea Scrolls: The Texts -- 3 The Qumran Community and Instruction in Law -- Appendix 1: Passages Containing the Terms midrash ha-torah and doresh ha-torah in the Dead Sea Scrolls -- Appendix 2: The Manuscript Evidence of the Rule of the Community (1QS) and the Text of the Council Rule (1QS VIII-IX) -- Appendix 3: The Role of the Community Council (ʿaẓat ha-yaḥad) within the Qumran Community -- Chapter 4 The Pharisees: Exegetes of the Laws -- 1 The Pharisees as Exegetes of the Laws: The Evidence from Josephus -- 2 The Scholarly View of exēgēsis as Interpretation of the Biblical Text and its Relation to midrash -- 3 The Meaning of ἐξηγέομαι -- 4 Exegesis in Legal Context: the Exegetes of the Eleusinian Mysteries